Personal health technology: A new era in cardiovascular disease prevention. Issue 2 (March 2015) - Franklin, Nina C.; Lavie, Carl J.; Arena, Ross A.
Abstract: Cardiovascular disease (CVD) remains the leading cause of morbidity and mortality worldwide yet the majority of related risk factors are largely preventable (primary prevention [PP]) and effectively treatable (secondary prevention [SP]) with healthy lifestyle behaviors. The use of information and communication technology (ICT) offers a unique approach to personal health and CVD prevention, as these mediums are relatively affordable, approachable, and accessible. The purpose of this review is to provide an overview of ICT-driven personal health technologies and their potential role in promoting and supporting self-care behaviors for PP and SP of CVD. In this review, we focus on technological interventions that have been successful at supporting positive behavior change in order to determine which tools, resources, and methods are most appropriate for delivering interventions geared towards CVD prevention. We conducted a literature search from a range of sources including scholarly, peer-reviewed journal articles indexed in PubMed and CINAHL, gray literature, and reputable websites and other Internet-based media. A synthesis of existing literature indicates that the overall efficacy of ICT-driven personal health technologies is largely determined by: 1) the educational resources provided and the extent to which the relayed information is customized or individually tailored; and 2) the degree of self-monitoring and levels of personalized feedback or other interactions (e.g. interpersonal communications). We conclude that virtually all the technological tools and resources identified (e.g. Internet-based communications including websites, weblogs and wikis, mobile devices and applications, social media, and wearable monitors) can be strategically leveraged to enhance self-care behaviors for CVD risk reduction and SP but further research is needed to evaluate their efficacy, cost-effectiveness, and long-term maintainability.